Sustaining the 3Rs - Rural, Regional and Remote Housing Markets in Western Australia - Rowley, Steven; McKenzie, Fiona Haslam (Pacific Rim Real Estate Society Conference, 2011)
The housing markets of non-metropolitan Australia are often ignored by both policy makers and academics. The factors influencing housing demand and supply in this diverse sector are not well understood and are often very different to urban markets. This paper explores a selection of rural, regional and remote (3R) housing markets within Western Australia and unpicks some of the issues which drive these markets. For example, the resources boom has had a dramatic affect on 3R towns in Western Australia with the demand for accommodation from mining companies and supporting organisations placing severe pressure on housing markets, both large and small. Resource industry-led demand has increased house prices and rents dramatically in some areas resulting in serious affordability issues for communities. However, even those towns without resource based industries have seen price growth in excess of metropolitan areas creating significant challenges for these communities and their policy makers. Using house price data for Western Australia, the paper explores how different 3R housing markets have been affected by a variety of economic conditions. The paper builds on the quantitative analysis by utilising results from four case study towns within the State. The case studies allow an exploration of the key supply and demand drivers in these towns and offer an insight into the unique circumstances influencing 3R housing markets in Australia. The paper concludes with a discussion of the challenges facing policy makers if they are to deliver thriving and sustainable communities in non-metropolitan Australia.